(3GdJMUjf aj UaGJ GdYGQajfs - (3GdCSOj, GdMdj, CHh GdYHGS, LeGd GdOjf, CMeO Hf eMeO Hf agO, J (B841(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj JLdi dYHGOg(B... (3CeG HYO agPG cJGH eVehfg GdYRdI hGdNehd(B...s
(3BNQgG (B:s
(3hGdeKbGd GdCQHYI hYTQhf bjQGWG CUZQgG eKd LHd CMO(B... (3bjd dg jG YHO Gddg CHTQ abO bHd(B...s
(3jSHbgG ChQGb ajgG CMGOjK eJaQbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U (B226s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B289s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B236s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B289s
Keywords: (3GdJUha hGdBOGH GdTQYjIs